Characterizing the secondary maximum in the r-band for Type Ia supernovae: diagnostic for the ejecta mass. Issue 2 (8th March 2019) - Papadogiannakis, Seméli; Dhawan, Suhail; Morosin, Roberta; Goobar, Ariel
ABSTRACT: An increase in the number of studied Type Ia supernovae (SNe Ia) has demonstrated that this class of explosions has a greater diversity in its observables than was previously assumed. The reasons (e.g. the explosion mechanism, progenitor system) for such a diversity remain unknown. Here, we analyse a sample of r -band light curves of SNe Ia, focusing on their behaviour ∼2–4 weeks after maximum light, i.e. the second maximum. We characterize the second maximum by its timing ($t_{r_2}$ ) and the integrated flux ($\overline{\mathcal {F}}_{r_2}$ ). We find that $t_{r_2}$ correlates with the 'colour–stretch' parameter sBV, which can be used as a proxy for 56 Ni mass, and $\overline{\mathcal {F}}_{r_2}$  correlates with the transparency time-scale, t 0 . Using $\overline{\mathcal {F}}_{r_2}$  for a sample of 199 SNe from the Palomar Transient Factory and intermediate Palomar Transient Factory, we evaluate a distribution on t 0 for a sample of SNe Ia found in an 'untargeted' survey. Comparing this distribution to the predictions of t 0 ranges from models we find that the largest overlap in t 0 values between models and observations is for the sub-Chandrasekhar double detonation models. We also compare our relations between t 0 and $\overline{\mathcal {F}}_{r_2}$  with that from the 1D explosion models of Goldstein & Kasen and confirm that $\overline{\mathcal {F}}_{r_2}$  can be used as a diagnostic of the total ejecta mass.